Postmodern Perspective of International Political Economy - Sujit Dutta; Debasish Nandy (Jurnal Perpajakan dan Keuangan Publik, 2025)
Postmodernism represents a literary trend that is evident in every era, leading to a variety of perspectives and conflicting scenarios. It is frequently described as a dramatic struggle that contests the principles of modernism. The features of postmodernism encompass indeterminacy, relativity, hybrid concerns, and a resistance to the profound void. Numerous forms of brief narratives exist, offering localized interpretations of events or issues that do not seek to transcend the spatial dimensions of time and space to achieve universality. The idea of a more extensive basis for legitimacy assessment is dismissed in favor of a logical examination of diverse narratives. This total relativity is the hallmark of postmodern epistemology. A crucial element of postmodernism is the indistinct boundary between reality and its representations. This paper investigates the postmodern viewpoint within the realm of international political economy, concentrating on transnational economic phenomena such as the movement of money and labor, currency accessibility, trade dynamics, exports, imports, protectionist measures, tariffs, non-tariff barriers, production processes, and the operations of multinational corporations. The objective is to clarify various dimensions of postmodernism in the context of international political economy. The content analysis method will be applied in this paper.